Temperature and Humidity Monitoring System over Plant and Uploading into the Cloud - Ghodke, VN; Pillai, Athul; S, Sahil; Pillay, Karan (International Journal of Computer Sciences and Engineering, 2022)
The ultimate goal of this project is to create an IoT (Internet of Things) based system that monitors temperature, humidity, and moisture from the farm. Temperature, humidity, and soil moisture sensors measure and process environmental conditions from the Arduino microcontroller. The actuator in this uses a pump to water the plants and lower their temperature. The obtained data from the sensor and the status of the actuator are sent to the Thing Speak server via the node MCU and can be remotely monitored. With the help of a smartphone or any other device. The collected data can be evaluated for various purposes. The results obtained are the effects of moisture, humidity, and pump water on the plants.